Presentación: "Sacrificios sensacionales Deleitando los sentidos en los Andes bolivianos" - Mendívil, Julio (2018)
Anthropologica starts the "Translations" section with an article by British ethnomusicologist Henry Stobart, one of the most important specialists in Bolivian indigenous music, particularly from the Potosí region.